1995
DOI: 10.5326/15473317-31-4-321
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in dogs with osteosarcomas of the flat or irregular bones

Abstract: The medical records of 45 dogs with histopathologically confirmed osteosarcomas arising from flat or irregular bones were reviewed. Thirty-five percent of the dogs eventually developed metastases. Telangectatic tumors and tumors arising from the rib and scapula had the highest prevalence of metastases. Survival times were short, with an overall median survival time of 120 days. Anatomic site, body weight, and completeness of surgical excision were found to be prognostic factors. Dogs with mandibular osteosarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
99
2
6

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 0 publications
9
99
2
6
Order By: Relevance
“…A relationship between radiographical appearance and uptake of Sm-153-EDTMP as reflected by the T/NTC ratio seems to suggest a higher ratio in tumours with more lytic (radiographic) lesions (Cases 1, 2, 3, 4, 5) than those with sclerotic changes (6,7,8). This might be explained by the fact that bone lysis is more indicative of an aggressive lesion that may have more reactive tissue and a greater blood supply and therefore accumulate more isotope 6,18 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A relationship between radiographical appearance and uptake of Sm-153-EDTMP as reflected by the T/NTC ratio seems to suggest a higher ratio in tumours with more lytic (radiographic) lesions (Cases 1, 2, 3, 4, 5) than those with sclerotic changes (6,7,8). This might be explained by the fact that bone lysis is more indicative of an aggressive lesion that may have more reactive tissue and a greater blood supply and therefore accumulate more isotope 6,18 .…”
Section: Discussionmentioning
confidence: 95%
“…The tumour was reported to be a chondrosarcoma of the humerus. In a recent report of osteosarcomas of the scapula, high prevalence of metastasis was found, with a short overall survival time (17 weeks) 8 . Partial scapulectomy combined with cisplatin therapy of primary bone neoplasia involving the proximal half of the scapula has also been reported; most cases developed metastatic lesions 24 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tumor grade, while prognostic in human osteosarcoma, 8 has historically not been consistently prognostic in studies of canine osteosarcoma with several studies showing no prognostic signifigance. 9,20 However, a recent study by Kirpensteijn et al showed a histologic grade of III to be an independent predictor of clinical outcome when cases of canine osteosarcomas from all locations in the body were evaluated. 11 The existence of a grading system that is significantly associated with survival for osteosarcomas, especially for this subset of osteosarcomas for which survival may be longer, would be invaluable for the clinical decision making process.…”
mentioning
confidence: 99%
“…Os locais de predileção do OSA são as regiões dos ossos longos (úmero, fêmur, raio, tíbia e ulna) (Liptak et al, 2004) com aproximadamente 25% dos tumores que surgem no esqueleto axial, incluindo os ossos planos do crânio, costelas, vértebras, esterno e pélvis (Hammer et al, 1995, Dickerson et al, 2001). …”
Section: Introductionunclassified